Increasing the Competitiveness of Batik Nusantara Through Products Innovative - Wufron, Wufron; Nurhasan, Rohimat; Hadita, Akmala; Zulfa, Siti Azizah; Handayani, Tia Fitria; Berliani, Syifa (Fakultas Ekonomi Universitas Garut, 2023)
The Nusantara batik industry has become an important part of Indonesia's cultural heritage and has significant potential to make a significant economic contribution. In an effort to enhance the competitiveness of Nusantara batik products, the concept of community partnership innovation has emerged as a promising approach. One concrete implementation of this approach is through the SANUTIK (Sapatu Nusantara Batik) program. This article will explain how community partnership innovation through SANUTIK can strengthen the Nusantara batik industry from various aspects. The research method used is descriptive and qualitative. Data analysis is conducted through SWOT analysis. The research results show that the SWOT Matrix Analysis of the internal conditions of Nusantara batik through SANUTIK has stronger strengths compared to weaknesses. The condition of Nusantara batik through SANUTIK has greater opportunities compared to threats. Nusantara batik through SANUTIK is in the aggressive/growth quadrant, which means it is in a prime and stable condition, making it highly possible to continue expanding, enhancing growth, and achieving maximum progress.